KONSEP MEDIA PEMBELAJARAN DALAM PERSPEKTIF ALQURAN - Rahimi Rahimi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2021)
Media comes from Latin which means intermediary. This meaning can be said as a communication tool used to carry information from a source to a recipient. The position of learning media by them is the process of learning media is a communication process and takes place in a system, then learning media occupies an important position as one of the components of the learning system. In this case, it will be related to the accuracy of the teacher in understanding the psychological condition of students, objectives, methods and completeness of aids. All of this belongs to the form of teaching either directly or indirectly. Al-Qur'anul Karim is the greatest miracle of Islam and its miracles always strengthen knowledge, He was revealed by Allah to His Messenger, Muhammad SAW to bring people out of a dark atmosphere into the light and guide them to the straight path.